Strategic Financial Management: Evidence from Seasoned Equity Offerings - BARCLAY, Michael (Institutional Knowledge at Singapore Management University, 2010)
Extant theories of capital structure assume myopic financial managers. So they have hard time to explain the financing behavior of seasoned equity offering (SEO) firms. In contrast with the pecking order theory, SEO firms typically are financially healthy companies with significant cash balances, low leverage, and unused debt capacity. At odds with the tradeoff theory, SEOs often move firms away from, rather than closer to, their target leverage ratios. SEOs appear to be driven by capital needs associated with large investment projects rather than by market timing considerations. Firms issue debt following the SEO to finance investment further and to increase leverage toward the target. We propose a broader theory of strategic financial management, in which rational CFOs manage capital structure strategically rather than myopically. They consider the firm's current and target leverage, long-term capital needs and cash flows as well as the costs and benefits of alternative sequences of financing transactions. This new framework well explains the financing and leverage behavior of SEO firms.